Styles of coping with stress and anxiety in young people from the Peruvian jungle during the health emergency - Garcia Garcia, Adan (2022)
Objective: To determine if there is a significant relationship between styles of coping with stressand anxiety in young people between the ages of 18 and 26 belonging to the San Martin region.Methodology: Quantitative approach, of a descriptive correlational type and a non-experimental, crosssectionaldesign. The population was 303 participants, obtained through a non-probability samplingfor convenience. For data collection, the Lima Anxiety Scale (EAL-20) and the Coping with StressQuestionnaire (COPE) were administered. Results: The results showed that there is a statisticallysignificant inverse relationship between two dimensions of stress coping styles, which are problemfocusedcoping and emotion-focused coping, and anxiety (rho = -0.367, p = 0.000; rho = -0.339, p =0.000 respectively).